If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 4a + 3 Reorder the terms: 15 = 3 + 4a Solving 15 = 3 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 15 + -4a = 3 + 4a + -4a Combine like terms: 4a + -4a = 0 15 + -4a = 3 + 0 15 + -4a = 3 Add '-15' to each side of the equation. 15 + -15 + -4a = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -4a = 3 + -15 -4a = 3 + -15 Combine like terms: 3 + -15 = -12 -4a = -12 Divide each side by '-4'. a = 3 Simplifying a = 3
| 4x-22=3x-17 | | 8z-11z=3z+42 | | 14x-56=6x | | 4x+18=22 | | 16X-192=0 | | 3x-5=16+2x | | 5x-9y=7 | | -5d=-20 | | 4x=3x+30 | | 3x-5=7-x | | =X^4-24x^2+80 | | 9y^2-30y+20=0 | | 47-4d=7-12d | | 3x-6=7-x | | 6x+5y=-25 | | 2y-3=21 | | 28-8x=x-8 | | -16=0.2b | | 3x+y=-23 | | Bx-2=K | | -9(-2)+4f=7f-3 | | 15x-9=12x+24 | | (k-7)*-5= | | -4(x-3)= | | 3a-7a=-12-2a | | 2x+2y=6 | | 7n-26=3n+6 | | 5h+2(h+3)= | | x^4+7x^3+5x^2-16x+6=0 | | 3-13y=11-5y | | 8x+8=2x-4 | | 2(7x+3)=76 |